2016
DOI: 10.1016/j.prro.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Distortion inherent to magnetic resonance imaging can lead to geometric miss in radiosurgery planning

Abstract: Purpose Anatomic distortion is present in all MRI data due to non-linearity of gradient fields and measures up to several millimeters. We evaluate the potential for uncorrected MRI to lead to geometric miss of the target volume in stereotactic radiosurgery (SRS). Methods and Materials Twenty-eight SRS cases were studied retrospectively. MRIs were corrected for gradient non-linearity distortion in three dimensions, and gross tumor volumes (GTVs) were contoured. The manufacturer-specified distortion field was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 30 publications
1
54
1
1
Order By: Relevance
“…All MR images were corrected for geometric distortions(28) prior to co-registration of the pre-RT MRI to the CT simulation images used in radiation treatment planning using custom software(9). The quality of this registration was confirmed visually slice-by-slice, and the resulting transformation matrix was used to resample the delivered radiation dose distribution from the treatment plan to the MRI volume space(9, 29). …”
Section: Methodsmentioning
confidence: 99%
“…All MR images were corrected for geometric distortions(28) prior to co-registration of the pre-RT MRI to the CT simulation images used in radiation treatment planning using custom software(9). The quality of this registration was confirmed visually slice-by-slice, and the resulting transformation matrix was used to resample the delivered radiation dose distribution from the treatment plan to the MRI volume space(9, 29). …”
Section: Methodsmentioning
confidence: 99%
“…However, the surgical procedure itself has remained relatively unchanged since its inception over thirty years ago (Benabid et al 1987, Sironi 2011). Although the surgical procedure varies from institution to institution, its success depends on the accurate placement of DBS electrodes into targeted brain structures, supported by precision stereotactic devices (Nakazawa et al 2014, Neumann et al 2015, Seibert et al 2016). The gold-standard traditional stereotactic system- the Leksell™ (Elekta, Stockholm, Sweden)- achieves this precision through a rigid head frame that remains affixed throughout the surgical planning and electrode placement to preserve the precision of the stereotactic coordinate space as mapped to the patient’s anatomy through MR images.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, increased conformity and presence of steep dose gradients in SRS treatment plans demand increased spatial accuracy in order to ensure effective treatment delivery, as spatial errors of just a few millimeters can induce considerable target underdosage, especially in tiny brain lesions. [6][7][8] Volumetric modulated arc therapy (VMAT) is commonly employed for SRS treatment delivery. Several studies have demonstrated that multiarc noncoplanar VMAT can deliver highly conformal plans to the target(s) and spare adjacent critical structures.…”
Section: Introductionmentioning
confidence: 99%